Decoding Digital Dystopia: Simulacra, Hyperreality, and Control in The Matrix Franchise Film Series as A Critique of Contemporary Society - Langoday, Yohanes Redan; Amir, Johar; Agussalim Aj, Andi (ppjbsip, 2025)
This study analyzes the representation of digital dystopia in The Matrix film series through Jean Baudrillard’s simulacra theory and Tom Moylan’s critical dystopia framework. Using qualitative analysis of key scenes and dialogues, the research traces the evolution of control mechanisms from physical oppression to psychological and biological manipulation. The franchise progresses through four stages of simulacra: reflection of reality (counterfeit), concealment (production), autonomous simulation, and hyperreality. Findings reveal how digital capitalism weaponizes narratives, eroding critical consciousness through algorithmic curation, deepfakes, and neuromarketing. While the films offer a robust critique of Western technocapitalism, their Eurocentric lens may overlook non-Western manifestations of digital authoritarianism, such as China’s Social Credit System. The study highlights real-world parallels, including social media’s role in polarization and AI’s capacity to hijack emotional networks. Practical implications call for algorithmic transparency, ethical AI governance, and critical digital literacy. Future research should explore dystopian narratives from the Global South to decentralize the discourse and address localized forms of digital oppression.Abstrak Penelitian ini menganalisis representasi distopia digital dalam serial film The Matrix melalui teori simulacra Jean Baudrillard dan kerangka distopia kritis Tom Moylan. Dengan analisis kualitatif terhadap adegan dan dialog kunci, penelitian ini melacak evolusi mekanisme kontrol dari penindasan fisik ke manipulasi psikologis dan biologis. Serial ini mengalami perkembangan melalui empat tahap simulacra: refleksi realitas (palsu), penyembunyian (produksi), simulasi otonom, dan hiperrealitas. Temuan mengungkapkan bagaimana kapitalisme digital mempersenjatai narasi, mengikis kesadaran kritis melalui kurasi algoritmik, deepfake, dan neuromarketing. Meski film ini memberikan kritik tajam terhadap teknokapitalisme Barat, sudut pandang Eurosentrisnya mungkin mengabaikan manifestasi otoritarianisme digital di luar Barat, seperti Sistem Kredit Sosial di Tiongkok. Studi ini menekankan paralel dunia nyata, termasuk peran media sosial dalam polarisasi dan kemampuan AI membajak jaringan emosional. Implikasi praktis menyerukan transparansi algoritma, tata kelola AI etis, dan literasi digital kritis. Penelitian lanjutan perlu mengeksplorasi narasi distopia dari Global Selatan untuk mendesentralisasi wacana dan mengatasi bentuk-bentuk penindasan digital yang terlokalisasi.